Groundwaters of Serbian and Slovenian Dinaric Karst – Comparison of Current status, Use, Protection and Perspectives. - Dejan Milenić; Metka Petrič (Acta Carsologica, 2009)
The Dinaric karst is the largest continuous karstland in Europe. With its outermost northwestern and eastern parts it extends to the territory of Slovenia and Serbia. Karst aquifers within it are very important sources of water supply in the two countries. We therefore decided to compare the characteristics of karst water resources and the approaches to the exploitation and protection of karst aquifers with the aim of searching for the most convenient methods for their research and management. Different characteristics of the two compared areas were established, as well as differences and similarities in the application of various research methods and the management approaches. The findings were summarized in the table which includes the most important parameters of karst water systems and research methods used for their study in the area of Dinaric karst in Serbia and Slovenia. As an example of good practice, two case studies are described in the article. For the Slovene part, vast experiences in the application of tracer tests with artificial tracers are reviewed and the guidelines for its efficient use in the research of karst aquifers are summarized. For the Serbian part, described case study of the detection of the pollution source in the recharge area of an important water source and the preparation of remedial measures are presented as an efficient approach to solve such problems on karst areas.